Integration Strategy for Infrastructure Development in MSME Product Marketing Systems in Serdang Bedagai Regency North Sumatra - Rusmewahni; Rodi Syafrizal (International Journal of Economics (IJEC), 2022)
Micro, Small and Medium Enterprises in the national economy have an important and strategic role. This condition is very possible because the existence of MSMEs is very dominant in the Indonesian economy, on the grounds that the number of industries is large and exists in every economic sector, has great potential in absorbing labor, and the contribution of MSMEs in the formation of GDP is very dominant. This study aims to find out how the Integration Strategy of Infrastructure Development in the MSME Product Marketing System in Serdang Bedagai Regency after the construction of the toll road in the Bengkel village. The method used in this research is Qualitative Descriptive Analysis with Miles and Huberman Model. Data analysis in qualitative research is carried out during data collection, and after completing data collection within a certain period. Activities in data analysis consist of the following steps : 1 . Data Reduction 2. Data Display 3. Conclusion Drawing/Verification. The results of the study show that the workforce used by MSMEs is getting smaller, there has been a significant decrease in income for MSME actors and even the closing of MSME merchant outlets / shops. by MSME traders in the Workshop Market in terms of product quality is quite good. However, existing products and creativity did not develop. In terms of prices offered in every store in the Workshop Market, it is still within reasonable and competitive limits.